2016
DOI: 10.1108/lodj-08-2012-0098
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of worker relations: the development of a three-component scale

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…The results of the validity test on the employee relations variable showed that 17 statement items had the value of r count> r table and 1 item statement had a value of r count <r table so that 1 item statement was invalid. Statement items for employee relations variables are taken from the article Gill & Meyer (2013) and Biggs (2013) with the following example "A harmonious culture of work communication exists within this organization". This can be said that 17 items statement about employee relations declared valid and 1 item statement declared invalid.…”
Section: Validity Testmentioning
confidence: 99%
“…The results of the validity test on the employee relations variable showed that 17 statement items had the value of r count> r table and 1 item statement had a value of r count <r table so that 1 item statement was invalid. Statement items for employee relations variables are taken from the article Gill & Meyer (2013) and Biggs (2013) with the following example "A harmonious culture of work communication exists within this organization". This can be said that 17 items statement about employee relations declared valid and 1 item statement declared invalid.…”
Section: Validity Testmentioning
confidence: 99%
“…In further applications of the resulting short scale, we will check whether, as expected, the reliability coefficient maintains good reliability for coefficients in all the factors. To cover the second limitation (the use of one item as a criterion), we will use another scale as a criterion, specifically the scale proposed by Biggs et al ( 2016 ), which presents partial validity evidence (based on relationships with other variables).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we will delve into validity based on relations to other variables that present convergent and discriminant evidence of the resultant scale following the multitrait-multimethod matrix proposed by Campbell and Fiske ( 1959 ). We will request completion of three different instruments from ~100 EHS workers: the scale we proposed; another scale with partial validity evidence to measure the work climate in EHS (the one proposed by Biggs et al, 2016 ); and the Safety Attitudes Questionnaire (Sexton et al, 2016 ), an instrument that measures safety climate, a construct similar to work climate although not exactly the same (work climate is considered wider). We expect to find high reliability coefficients in the three instruments, a high correlation between the two instruments that measure work climate in EHS (convergent evidence) and a low correlation (at least lower than that obtained in the convergent evidence study) between our instrument and the one that measures a different construct (discriminant evidence).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study proposes that salary satisfaction and work relationship may be the significant factors for enhancing individual performance (Biggs et al 2016;Gupta et al 2012). However, it has been little attempts to investigate the influences of salary satisfaction and work relationship on the performance dimensions as mentioned.…”
Section: Introductionmentioning
confidence: 99%